Power module sintering method and power module
By adopting a disposable all-copper sintering method in the power module package, the problems of cumbersome processes and low reliability of aluminum wire bonding wires in the prior art are solved, and the high-temperature reliability and heat dissipation performance are improved, and the process flow is simplified. Reduced thermal resistance.
Patent Information
- Application Number
- CN202411746523.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing power module packaging technology has cumbersome process flow, aluminum wire bonding wires are easily fused and mismatched, resulting in low reliability, and tin-based soldering has poor performance at high temperatures, which affects the heat dissipation effect.
A power module sintering method is adopted to form a copper sintering layer by printing copper paste or copper film on the base plate and copper-clad ceramic plate, drying, assemble the chip and performing single-copper sintering at high temperature using a soft press head to form a copper sintering layer, simplifying Process flow and improve high temperature reliability and heat dissipation performance.
The process flow is simplified, the high-temperature reliability and heat dissipation performance of the module are improved, the thermal resistance is reduced, the reliability problems of tin-based solder is avoided, and the stable operation of the device is ensured under high temperature and high power conditions.
Smart Images

Figure CN119230427A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor packaging, and in particular to a power module sintering method and a power module. Background Art
[0002] As an important component of energy conversion, the chip needs to be protected. Therefore, a reasonable packaging structure is required to ensure the chip's electrical connection, heat dissipation, reliable mechanical support and environmental protection. Generally, the electrical connection between the chip and the substrate or lead frame is achieved through welding (sintering) and wire bonding.
[0003] With the rapid development of power electronics technology in photovoltaics, rail transportation, automotive electronics and other fields, chips are developing towards higher power density, switching frequency and smaller chip size, which puts higher requirements on packaging technology.
[0004] For power devices, the weakest reliability points are usually the chip bonding wires and the connection between the substrate and the heat sink. The bonding wires are usually made of aluminum wires, which have weak current capacity and low melting point, and there is a risk of melting due to overheating. The thermal expansion mismatch between the aluminum wire and the substrate and the Kirkendall void effect make the bonding wires more likely to fall off. The connection between the substrate and the heat sink is larger, so the accumulated thermal stress caused by the thermal expansion mismatch will be more serious and it is also more likely to fail.
[0005] Moreover, there are currently many steps to seal a complete module, such as Figure 1 As shown, it includes one printing, patch, one welding, one cleaning, one bonding, two printing, two chip mounting, two welding, two cleaning, two bonding, etc. That is, first, the chip is welded on the DBC substrate, and then the flux is cleaned. In order to avoid the remelting of the material used in the first welding, the melting points of the materials used in multiple welding are different, which will further aggravate the problem of mismatch of thermal expansion when the temperature changes. Next, the chip is bonded with aluminum wire to complete the electrical connection between the chip and the circuit. After that, the second welding is carried out to weld the DBC substrate to the radiator. After the welding is completed, it is cleaned again. Then the second bonding is carried out, and finally, the glue is poured or plastic sealed. The whole process has a long step. Although there is a sintering process (such as sintering silver or sintering copper for the solder layer), which can reduce the two-step cleaning operation, the aforementioned problems still exist, and more cumbersome steps are required, resulting in a long process flow, affecting the production progress and reliability.
[0006] Therefore, in order to solve the above problems, a highly reliable and efficient power module sintering method and a power module are needed. Summary of the invention
[0007] One of the purposes of the present invention is to provide a power module sintering method, which can simplify the sintering steps and improve high temperature reliability and heat dissipation performance.
[0008] In order to solve the above technical problems, this application provides the following technical solutions: A power module sintering method, comprising the following contents: S1, printing a preset copper paste pattern or pasting a preset copper film on the surface of the base plate and the copper-clad ceramic plate respectively; if it is a copper paste, jump to step S2, if it is a copper film, jump to step S3; S2, drying the copper paste on the base plate and the copper-clad ceramic plate; S3, assembling the copper-clad ceramic board on the base plate, assembling the chip on the copper-clad ceramic board, and placing a copper top connector or Cu-Clip on the upper layer of the chip to obtain an assembly; S4. The assembly is pressed by a heat-softened soft pressing head and then sintered. During the sintering process, the soft pressing head is softened by heat and pressed against the base plate, the copper-clad ceramic plate, the chip and the copper top connector or Cu-Clip. After sintering, a copper sintering layer is formed between the copper-clad ceramic plate and the base plate, between the copper-clad ceramic plate and the chip, and between the chip and the copper top connector or Cu-Clip.
[0009] Furthermore, the copper-clad ceramic board includes DBC, AMB or DPC.
[0010] Furthermore, in step S2, the drying temperature of the copper-clad ceramic board is 100-180° C., and the drying time is 5-15 min; the drying temperature of the base plate is 100-180° C., and the drying time is 15-40 min.
[0011] Furthermore, in step S4, the sintering is performed for 10-30 min at 220-280° C. and 10-20 MPa pressure in an atmosphere of nitrogen, formic acid or mixed hydrogen.
[0012] Furthermore, the distance between the top surface of the bottom plate and the top surface of the copper top connector or Cu-Clip is a, and the thickness of the soft pressing head is greater than or equal to a.
[0013] Furthermore, in step S4, the soft pressure head is a hard pressure head with a soft pad, or a pressure head made of soft material.
[0014] Furthermore, the cushion is made of silicone, fluororubber, polyurethane or polyimide.
[0015] Furthermore, the thickness of the cushion is 0.6-2 mm.
[0016] The second object of the present invention is to provide a power module, which includes, from bottom to top, a base plate, a copper-clad ceramic plate, a chip and a copper top connector or Cu-Clip; a copper sintered layer is formed between the bottom of the copper-clad ceramic plate and the base plate, and a copper sintered layer is formed between the top of the copper-clad ceramic plate and the bottom of the chip.
[0017] This solution uses a soft press head to achieve a one-time sintering process of welding chips, Cu-Clip / DTS, DBC, and baseplate at the same time, which can save process flow. The all-copper interconnection structure can achieve the high-temperature and high-reliability packaging goals of the module, improve the device's flow capacity, and effectively reduce the device's thermal resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 A schematic diagram of an existing chip packaging method; Figure 2 A flow chart of a power module sintering method according to an embodiment; Figure 3 A schematic diagram of a finished product of a power module according to an embodiment of the present invention; Figure 4 It is a schematic diagram of the change of the mean value of the thermal resistance of the solder layer before and after the reliability test of a power module sintering method in an embodiment; Figure 5 A schematic diagram of the void situation before and after the reliability test of a power module sintering method in an embodiment; Figure 6 This is a schematic diagram of the change in the mean value of the thermal resistance of the solder layer before and after the reliability test of the existing solution using solder paste; Figure 7 This is a schematic diagram of the solder layer void situation before and after the test of the existing solution using solder paste; Figure 8 Schematic diagram of the electrical performance test results of the chip before and after the reliability test. DETAILED DESCRIPTION
[0019] The following is further described in detail through specific implementation methods: The symbols in the drawings of the specification include: base plate 1, DBC 2, chip 3, Cu-Clip 4, copper sintered layer 5. Example
[0020] like Figure 2 As shown, a power module sintering method of this embodiment includes the following contents: S1, printing step: printing a preset copper paste pattern or pasting a preset copper film on the surface of the base plate and the copper-clad ceramic board, respectively, with the pattern area slightly larger than the chip mounting area; if it is copper paste, jump to step S2, if it is copper film, jump to step S3; Specifically, a preset pattern is printed on the top surface of the bottom plate. In this embodiment, the bottom plate has a heat dissipation function. In order to further enhance the heat dissipation capability, fins may be provided at the bottom of the bottom plate.
[0021] The copper-clad ceramic board includes DBC (direct copper-clad ceramic substrate), AMB (active metal brazed ceramic substrate), DPC (directly plated ceramic substrate), or other materials that can be used as a substrate. This embodiment takes DBC as an example for description.
[0022] S2, drying step: drying the copper paste on the bottom plate and the DBC, wherein the DBC drying temperature is 100-180° C., and the drying time is 5-15 min; the bottom plate drying temperature is 100-180° C., and the drying time is 15-40 min; S3, patch step: assemble the DBC on the base plate through the positioning tool, assemble the chip on the DBC, and place the copper top connector (DTS) or Cu-Clip on the upper layer of the chip to obtain an assembly; S4, sintering step: the assembly is placed in a sintering device, and the sintering device applies pressure to the assembly through a heat-softened soft pressure head, and sintering is carried out for 10-30 minutes at 220-280°C and 10-20MPa pressure, and the atmosphere is nitrogen, formic acid or mixed hydrogen atmosphere; specifically, the pressure is generated by the pressure booster of the sintering device, and the pressure is applied to the assembly by the heat-softened soft pressure head. Industrial mixed hydrogen is generally 10% or 5% hydrogen added to the nitrogen atmosphere.
[0023] Among them, the soft indenter is a soft pad on the existing hard indenter, or a soft material indenter is directly used; the soft pad is made of silicone, fluororubber, polyurethane or PI (polyimide). The soft material indenter and the soft pad are made of the same material. The soft indenter will soften during the sintering process, so that the soft indenter can adapt to the surface of the assembly after softening, and can press against the bottom plate, copper-clad ceramic board, chip and copper top connector or the top surface of Cu-Clip, reducing the probability of cracking during the one-time sintering pressurization process, so that one-time sintering can be achieved.
[0024] That is, the soft pressing head is used so that during the sintering process, the soft pressing head can be further softened by heating and fully cover all levels of the assembly to make the force uniform. Therefore, the distance from the top surface of the bottom plate to the top surface of the copper top connector or Cu-Clip is a, and the thickness of the soft pressing head is greater than or equal to a, so as to fully cover and press all parts of the assembly to avoid local force and cracking. For example, the thickness of the soft pad is 0.6-2mm to match the depth of the chip, Cu-Clip and AMB etching groove. Compared with the hard pressing head, it can effectively avoid the problem of DBC cracking during the pressure application process.
[0025] Since copper paste or copper film is printed between DBC and the base plate, copper paste or copper film is printed between DBC and the chip, and there is copper contact between the chip and the copper top connector or Cu-Clip, full copper sintering is achieved; after sintering, a copper sintering layer is formed between DBC and the base plate, between DBC and the chip, and between the chip and the copper top connector or Cu-Clip; S5, bonding step: bonding the sintered assembly; S6. Plastic encapsulation or casing filling with glue is performed to obtain a power module with full copper interconnection.
[0026] like Figure 3 As shown, using the above method, this embodiment also provides a power module, which includes, from bottom to top, a base plate 1, a copper-clad ceramic plate, a chip 3 and a copper top connector or Cu-Clip 4; in this embodiment, the copper-clad ceramic plate adopts DBC2, and DBC2 includes an upper copper foil, an intermediate ceramic layer and a bottom copper foil; a copper sintered layer 5 is formed between the bottom copper foil and the base plate, and a copper sintered layer 5 is formed between the upper copper foil and the bottom of the chip 3; Cu-Clip 4 is used on the top, and a copper sintered layer 5 is formed between the top of the chip 3 and Cu-Clip 4; a full copper interconnection structure is formed.
[0027] The existing packaging process is cumbersome and usually requires multiple printing, sintering and welding, which increases production costs and time. Devices that use aluminum wire for bonding show low reliability when working at high temperatures for a long time and are prone to failure due to thermal expansion or mechanical stress. Tin-based solder has poor performance in high-temperature environments and is prone to thermal failure, making it unsuitable for high-temperature and high-reliability packaging requirements. At the same time, tin-based solder has poor thermal conductivity, which increases the thermal resistance of the device and affects the heat dissipation effect of the device.
[0028] The thermal resistance of the 1200V, 200A module is used as an example for performance comparison. At the same time, the average thermal resistance of the solder layer before the module test is measured to be 0.0173. The thermal resistance of the solder layer during the test is tested and the average is taken: This method uses sintering conditions 1: 260°C, 10MPa, 10min; the reliability test is shown in Table 1: Table 1 Device thermal resistance Module thermal resistance vs. solder paste module thermal resistance reliability Failure conditions 0.0754 Module thermal resistance is 8.9% lower -55-150℃ 3000cycles Among them, at 3000 cycles, the module failed.
[0029] This method uses sintering condition 2: 220℃, 20MPa, 30min; the reliability test is shown in Table 2: Table 2 Device thermal resistance Module thermal resistance vs. solder paste module thermal resistance reliability Failure conditions 0.0736 Module thermal resistance is 11.11% lower -55-150℃ 3000cycles Among them, at 3000 cycles, the module failed.
[0030] Combined with the above experiments, failure analysis was performed to check the thermal resistance of the solder layer before and after the reliability test, and the void situation of the solder layer before and after the reliability test.
[0031] The average change of thermal resistance of solder layer before and after reliability test is as follows Figure 4 As shown in the figure, after 3000 cycles of temperature shock, the average thermal resistance of the solder layer decreased by 31.8%.
[0032] Since the copper solder layer further diffuses at low temperature along the thermal stress gradient to complete densification, the porous structure formed by one-time sintering is not completely densified. It will be further densified during the reliability test, which will reduce the thermal resistance and be more conducive to later use.
[0033] The void situation before and after the solder layer reliability test is as follows Figure 5 As shown, the left side shows the void situation of the solder layer before the test, and the right side shows the void situation of the solder layer after the test. It can be seen that there is no void in the copper solder layer before and after the reliability test.
[0034] Combining the above test results, the cause of failure is: the chip failed, the solder layer did not fail, and the performance of the packaging material was better than the chip.
[0035] The existing solution using solder paste is: the first soldering is 15 minutes, using Pb90Sn10 high-lead solder paste, and the module is cleaned for 15 minutes; the second soldering is 20 minutes, using SAC305 solder, the module is cleaned for 15 minutes, and the thermal resistance of the solder layer and the voids of the solder layer are detected before the test; the reliability test is shown in Table 3: Table 3 Device thermal resistance Thermal resistance change reliability Failure conditions 0.0828 Increase by more than 20% -55-150℃ 1500cycles Among them, the module failed at 1500 cycles, and the thermal resistance of the one-time all-copper sintered power module was lower than that of the solder paste device before the thermal resistance test.
[0036] The average change of thermal resistance of solder layer before and after reliability test is as follows Figure 6 As shown, it can be obtained that the thermal resistance of the solder layer increased by 30.9% before and after the reliability test, while in the industry, a 20% increase in thermal resistance is considered a failure.
[0037] like Figure 7 The solder layer void conditions before and after the test are shown (the left side is the solder layer void conditions before the test, and the right side is the solder layer void conditions after the test). It can be seen that the voids in the solder layer increase significantly before and after the failure of the solder paste soldered device.
[0038] Combined with the above test results, it can be concluded that the reason for module failure during solder paste welding is that the failure of the solder paste soldering layer leads to test failure.
[0039] It can be seen from the test results of Table 1 and Table 2 of the present method and Table 3 of the existing solution that the module sintered by the present method has lower thermal resistance and higher reliability.
[0040] In order to further verify, the electrical performance of the chip was tested before and after the reliability test. The test results are as follows: Figure 8As shown in the figure, ID is defined as the maximum continuous current allowed when the chip is at the maximum rated junction temperature TJ(max) and the tube surface temperature is 25°C or higher. Vds is the maximum drain-source voltage, that is, the maximum voltage that can be applied before the drain-source avalanche breakdown occurs. This figure shows the output characteristic curve of MOSFET (metal oxide semiconductor field effect transistor). As the voltage continues to increase, the current continues to increase until the set current value of the MOSFET.
[0041] After the temperature shock before and after the reliability test, Vds increased from 3.978 to 4.22V, an increase of 6.08%. It is generally believed that if Vds increases by more than 5%, the chip will fail. Although the overall thermal resistance of the copper paste package still meets the industry standard, the chip performance is degraded. It can be seen that the overall performance thermal resistance is reduced before and after the full copper one-time sintering test, and the structure has no obvious change. The chip has a certain performance degradation.
[0042] It can be concluded that one-time full copper sintering has lower thermal resistance and higher reliability.
[0043] The reason why the existing technology uses a complex process is that the chip is the main heat source, so high-temperature solder paste is needed to match the packaging requirements. At the same time, in order to avoid repeated melting of welding materials during multiple welding processes, high-temperature solder paste with different melting points is needed for welding, but this will make the material composition more complicated, further aggravating the problem of thermal expansion mismatch. If one-time molding is used, the multi-layer structure will lead to uneven pressure, so during the one-time sintering process, the device is prone to cracking during the pressure process.
[0044] In this embodiment, through soft pressing, the components can be softened and pressed at the same time during the one-time sintering process, so that the force is more uniform, the possibility of cracking is significantly reduced, and the chip, Cu-Clip / DTS, DBC / AMB and the base plate can be welded at the same time. And because it is a one-time sintering, the structure of all copper sintering can be achieved in one time, so that the overall material can not only use a relatively uniform thermal expansion coefficient or the same material, but also requires the same material to be more in line with the conditions of one-time sintering and have better performance, significantly improving the problem of thermal expansion mismatch, and optimizing electrical and mechanical properties. It also simplifies the traditional multi-step process, reduces production time and complexity, and significantly reduces the thermal resistance of the device, improves the heat dissipation effect, thereby ensuring that the device can still maintain stable operation under high temperature and high power conditions. Through one-time sintering and copper interconnection structure, the reliability problem of tin-based solder is also avoided, so that the packaging structure can meet the needs of high temperature and long-term stable operation, greatly improving the overall packaging quality and reliability.
[0045] The above are only embodiments of the present invention. The invention is not limited to the fields involved in this implementation case. The common sense such as the known specific structures and characteristics in the scheme is not described in detail here. The ordinary technicians in the relevant field know all the common technical knowledge in the technical field to which the invention belongs before the application date or the priority date, can obtain all the existing technologies in the field, and have the ability to apply the conventional experimental means before that date. The ordinary technicians in the relevant field can improve and implement this scheme in combination with their own abilities under the enlightenment given by this application. Some typical known structures or known methods should not become obstacles for ordinary technicians in the relevant field to implement this application. It should be pointed out that for those skilled in the art, without departing from the structure of the present invention, several deformations and improvements can be made, which should also be regarded as the protection scope of the present invention, which will not affect the effect of the implementation of the present invention and the practicality of the patent. The protection scope required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to explain the content of the claims.
Claims
1. A power module sintering method, characterized in that: It includes the following: S1, printing a preset copper paste pattern or pasting a preset copper film on the surface of the base plate and the copper-clad ceramic plate respectively; if it is a copper paste, jump to step S2, if it is a copper film, jump to step S3; S2, drying the copper paste on the base plate and the copper-clad ceramic plate; S3, assembling the copper-clad ceramic board on the base plate, assembling the chip on the copper-clad ceramic board, and placing a copper top connector or Cu-Clip on the upper layer of the chip to obtain an assembly; S4. The assembly is pressed by a heat-softened soft pressing head and then sintered. During the sintering process, the soft pressing head is softened by heat and pressed against the base plate, the copper-clad ceramic plate, the chip and the copper top connector or Cu-Clip. After sintering, a copper sintering layer is formed between the copper-clad ceramic plate and the base plate, between the copper-clad ceramic plate and the chip, and between the chip and the copper top connector or Cu-Clip.
2. The power module sintering method according to claim 1, characterized in that: The copper-clad ceramic board includes DBC, AMB or DPC.
3. The power module sintering method according to claim 1, characterized in that: In the step S2, the drying temperature of the copper-clad ceramic board is 100-180° C., and the drying time is 5-15 minutes; the drying temperature of the bottom plate is 100-180° C., and the drying time is 15-40 minutes.
4. The power module sintering method according to claim 1, characterized in that: In the step S4, sintering is performed for 10-30 min at 220-280° C. and 10-20 MPa pressure in an atmosphere of nitrogen, formic acid or mixed hydrogen.
5. The power module sintering method according to claim 1, characterized in that: The distance between the top surface of the bottom plate and the top surface of the copper top connector or Cu-Clip is a, and the thickness of the soft pressing head is greater than or equal to a.
6. The power module sintering method according to claim 1, characterized in that: In step S4, the soft pressure head is a hard pressure head with a soft pad, or a pressure head made of soft material.
7. The power module sintering method according to claim 6, characterized in that: The soft pad is made of silicone, fluororubber, polyurethane or polyimide.
8. The power module sintering method according to claim 6, characterized in that: The thickness of the soft pad is 0.6-2 mm.
9. A power module, characterized in that: From bottom to top, it includes a base plate, a copper-clad ceramic plate, a chip and a copper top connector or Cu-Clip; a copper sintered layer is formed between the bottom of the copper-clad ceramic plate and the base plate, and a copper sintered layer is formed between the top of the copper-clad ceramic plate and the bottom of the chip; a copper sintered layer is formed between the top of the chip and the copper top connector or Cu-Clip; the power module as a whole forms a full copper interconnection structure.
Citation Information
Patent Citations
Power module and packaging method thereof
CN116053144A
High-thermal-conductivity nano-copper composite soldering paste as well as preparation method and application thereof
CN117862733A
Low thermal resistance H bridge
CN205960972U
Inspection device for semiconductor device
JP1997178808A
Method for bonding electronic component
JP2014179420A
Cited By
Discrete device copper sintering and crimping device and preparation method
CN121604841A
